Modelling and simulation of skyhook controllersemi-active suspension system - Saiful Amin, Kamaruddin (2012)
The purpose of this project is to modeling and simulates the skyhook controller for semi-active suspension system for a quarter car model. There are two parts to be developed in this study namely, the hydraulic model and force tracking controller. The simulation of this system will be determined by performing computer simulations using the MATLAB and SIMULINK toolbox. The data for each parameter were obtained from the research that have done previously. The simulation results show that the semi-active suspension system could provide significant improvements in the ride quality and road handling compare with the passive suspension system.